-x-y=-9
-3x-2y=-28
eliminate the x first
multiply the first system of equations by 3
(3)(-x)=-3x
(3)(-y)=-3y
(3)(-9)=-27
-3x-3y=-27
-3x-2y=-28
eliminate the systems of equations by subtracting
-3x--3x-3y--2y=-27--28
-3x+3x-3y+2y=-27+28
-y=1
multiply -1 for -y=-1 to get positive y
(-y)(-1)=(1)(-1)
y=-1
substitution method by using y=-1 into one of the system of equations
-x-y=-9
-x--1=-9
-x+1=-9
move +1 to the other side
sign changes from +1 to -1
-x+1-1=-9-1
-x=-10
multiply by -1 for -x=-10 to get positive x
(-x)(-1)=(-10)(-1)
x=10
answer:
x=10, y=-1